“The Stakes Are Higher”- Patient and Caregiver Perspectives on Cystic Fibrosis Research and Personalized Medicine - Knoppers, Terese; Cosquer, Marie; Hagan, Julie; Nguyen, Minh Thu; Knoppers, Bartha Maria (Frontiers in Medicine, 2022)
Introduction: Making bench to bedside advances in cystic fibrosis (CF) care requires the sustained engagement and trust of people living with CF. However, there is a scarcity of studies exploring their concerns and priorities regarding research and its end products. The aim of this qualitative study is to generate empirical evidence regarding CF patient and caregiver perspectives on research and personalized medicine to foster developments in translational research in Canada. Methods: A total of 15 focus groups were conducted, engaging 22 adults with CF and 18 caregivers (e.g., parents, siblings and spouses) living in Canada. Inductive thematic analysis relied on an iterative process involving themes derived from both participant meaning-making and existing scientific literature. Participant perspectives were considered along intrapersonal, intracommunity, interpersonal, and structural lines. Results: Overall, participants described a relationship to CF research inextricable from the lived experience of CF as a lifelong progressive and terminal disease and from the goal of advancing medical science. They were enthusiastic and excited about the emergence of CFTR modulators, although they had some knowledge gaps regarding the associated research. They largely spoke to positive experiences with researcher communication but had feedback regarding informed consent processes and the return of study results. Participants also voiced concerns about structural access barriers to research and to its end products. Extensive histories of research participation, a relatively small and intercommunicative CF community, and structural overlap between research and care settings contributed to their perspectives and priorities. Conclusion: Study findings are valuable for researchers and policy-makers in CF and rare or progressive diseases more broadly. Continuing to solicit and listen to the voices of patients and caregivers is crucial for research ethics and the translation of new therapies in the area of personalized medicine.